Antisemitism [videorecording (DVD)] - Ziv, Ilan; Brakni, Rachida, 1977- (Icarus Films Home Video, 2022)
This documentary masterfully traces the history of antisemitism and its effects, from cartoon-like medieval church iconography showing Jews with funnels on their heads to WWII propaganda comparing Jews to rats and new-Nazis marching in the streets of modern day France. How did we get from saying never again after the Holocaust to murders of French Jewish children and calls for the expulsion of Jews from western democracies? To answer that question, director Ilan Zive focuses on key events from the last 150 years, including the Dreyfus Affair, the first widely disseminated antisemitic texts. While it takes a broad, sweeping approach, Ziv maintains a steadfast focus on human stories. We meet the descendants of Alfred Dreyfus and the heartbroken son of murdered 85-year-old Holocaust survivor Mireille Knoll, killed by a young neighbor because he assumed since she was Jewish she would have money.